Milly, Molly and BushBob - Pittar, Gill; Morrell, Cris (Milly Molly Books Gisborne, N.Z., 2001)
Where is BushBob and will his love of nature bring him home? Another in the series where every story has a message with a value such as honesty, responsibility, tenacity, kindness, self-sufficiency, acceptance of difference, to name a few